Transforming Institutions Undergraduate STEM Education for the 21st Century - Weaver, Gabriela; Burgess, Wilella (Purdue University Press, 2015)
Higher education is coming under increasing scrutiny, both publically and within academia, with respect to its ability to appropriately prepare students for the careers that will make them competitive in the 21st-century workplace. At the same time, there is a growing awareness that many global issues will require creative and critical thinking deeply rooted in the technical STEM (science, technology, engineering, and mathematics) disciplines. Transforming Institutions brings together chapters from the scholars and leaders who were part of the 2011 and 2014 conferences. It provides an overview of the context and challenges in STEM higher education, contributed chapters describing programs and research in this area, and a reflection and summary of the lessons from the many authors' viewpoints, leading to suggested next steps in the path toward transformation.